ANALYSIS OF FACTORS THAT INFLUENCE THE INCLUSION OF PREGNANT WOMEN IN HIV TESTIN PUSKESMASSIMPANG KERAMATNORTH ACEH DISTRICT IN 2020 - ana, mariana (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
The problem of Human Immunodeficiency Virus (HIV) and Acquired immune deficiency syndrome (AIDS) in Indonesia is one of the national health problems that requires comprehensive joint digestion. In pregnant women, HIV is a threat to the safety of the soul of the mother and her baby, because transmission occurs from mother to baby. More than 90 percent of HIV transmission in children is obtained vertically due to transmission from mother to baby. The purpose of this study was to analyze the factors that influence the participation of pregnant women in HIV testing at Simpang Keuramat Public Health Center in North Aceh Regency in 2020. This type of research is an observational study with a case-control design. The sampling technique in this study was using puposive sampling technique.. Data analysis in this study used univariate, bivariate and multivariate analysis. The results of multivariate analysis were found to be knowledgeable because a value of p <0.05 was found. obtained an OR of 12,108 with 95% CI 4,700-31,193 means that the exclusion of pregnant women for HIV testing is 12,108 times the possibility of having less knowledge than pregnant women who have good knowledge. It is expected that health workers will focus more on health services for pregnant women to equalize reproductive health and child health and make it easier for pregnant women to get HIV testing health services.